Greater Performance of Exotic Elodea nuttallii in Response to Water Level May Make It a Better Invader Than Exotic Egeria densa During Winter and Spring - Wang, Yalin; Chen, Xiuwen; Liu, Junchu; Hong, Yaping; He, Qiankun; Yu, Dan; Liu, Chunhua; Dingshanbayi, Huanjiang (Frontiers in Plant Science, 2019)
The strategy of producing rapid initial growth and establishing early in the growing season is important, and it is employed by invasive macrophytes. Elodea nuttallii and Egeria densa, two Hydrocharitaceae species, became weeds after invading many countries in recent years. Comparative studies on their invasive traits in relation to native species during winter and spring are limited. In the present study, we compared the growth performance of these two exotic species with a perennial native species Potamogeton maackianus under different water depths (1 m, 2 m and 3 m) during winter (January and February) and spring (March and April). Three morphological traits (shoot number, root number and shoot length), total biomass, relative growth rate (RGR) and two physiological photosynthetic traits (total chlorophyll content and the maximum quantum yield of PSⅡ (Fv/Fm)) were measured for each macrophyte. All three species could overwinter as entire leafy plants. Biomass, RGR, morphological traits and physiological traits were all different among species. However, water depths had a significant effect only on morphological traits. At all water depths, E. nuttallii had significantly higher values for morphological traits, total biomass and RGR than P. maackianus, while E. densa had significantly fewer value roots and a lower total chlorophyll content than P. maackianus. Except for Fv/Fm at a 3 m water depth, all morphological and physiological photosynthetic traits, biomass and RGR of E. nuttallii were all significantly higher than those of E. densa. In addition, a large amount of adventitious roots developed from E. nuttallii but not from the other two species. These results indicate that the advantages of E. nuttallii to grow in winter and spring may make it more prone to expansion in China than E. densa.